Anti-Unwinding Sliding Mode Attitude Maneuver Control for Rigid Spacecraft - Dong, Rui-Qi; Wu, Ai-Guo; Zhang, Ying (IEEE transactions on automatic control, 2022)
In this article, anti-unwinding attitude maneuver control for rigid spacecraft is considered. First, in order to avoid the unwinding phenomenon when the system states are restricted to the switching surface, a novel switching function is designed by a hyperbolic sine function such that the switching surface contains the two equilibriums. Then, a sliding mode attitude maneuver controller is developed based on the proposed switching function to ensure the robustness of the closed-loop system to disturbance and inertia uncertainty. Another important feature of the presented attitude control law is that a dynamic parameter is constructed to guarantee the unwinding-free performance before the system states reach the switching surface. Furthermore, a boundary layer is introduced for the designed controller to avoid the chattering phenomenon. Moreover, the convergence property and unwinding-free performance when the system states within the boundary layer are proven. The simulation results demonstrate that the unwinding problem is settled during attitude maneuver for rigid spacecraft by adopting the newly developed switching function and the presented attitude control scheme.